Thoughts from a past AGU SPA fellows committee - Halford, Alexa J.; Burrell, Angeline G.; Yizengaw, Endawoke; Bothmer, Volker; Carter, Brett A.; Raymond, John C.; Maute, Astrid; Samara, Marilia; Maruyama, Naomi; Alves, Livia R. (Frontiers in Astronomy and Space Sciences, 2022)
Community honours, such as those bestowed by professional scientific societies like the American Geophysical Union (AGU) are an important element of both individual career advancement and contributes to the historical record of scientific progress. The process by which honours are bestowed is not widely shared amongst the community. The purpose of this article is to share the recent experiences of several members of the AGU Space Physics and Aeronomy (SPA) Fellows committee. We outline the criteria for selection, the evaluation process, difficulties encountered by the committee, and steps taken to mitigate these difficulties. Of particular note is the impact of implicit bias in the award system. Steps could be taken by the awarding scientific societies to reduce the impact of these biases, but in the meantime individual award committees can employ some of the strategies we outline in this article. By sharing our experiences, we hope to improve process of granting awards and honours for the scientists putting together award nominations, future committee members, and the scientific societies granting these awards.